Internal Control System, Accounting Record, Financial Reporting In Toko Marion - Sukiantono Tang; Sherly Marlina (ConCEPt - Conference on Community Engagement Project, 2023)
This activity was done to apply accounting knowledge learned during the university study to daily business practice. Besides, this activity also aims to help micro-business entrepreneurs make accounting records and financial reports correctly and accurately to reflect the actual business situation. The object of this activity is Toko Marion, a micro-business that still uses manual records on books, also not having a financial report. These conditions were known by visiting the business place and also by interviewing. This activity results in an accounting system designed in Microsoft Access program so that entrepreneurs can easily do the records and the system can automatically create financial reports. This system can also improve business flow to a more efficient and effective business operation.